PMM.34 Screening and Management of Gestational Diabetes Mellitus in Scottish Units: A National Survey. (9th June 2014) - Stirrat, LI; Denison, FC; Love, CDB; Lindsay, RS; Reynolds, RM
Abstract : Background: The last national survey of screening practices for gestational diabetes (GDM) in the UK in 1999 concluded that a lack of consensus about screening was due to a lack of clinical guidelines. 1 Since then, new clinical guidelines have defined risk factors for GDM, and suggested that diagnosis should be made at a lower level of hyperglycaemia than previously recommended. This study aimed to determine current practices for screening and management of GDM in Scotland. Methods: An online questionnaire was designed to investigate the screening and management of GDM. It was distributed to all maternity units in Scotland managing women with GDM (n = 15) for completion by Consultant Obstetricians, Diabetologists or other relevant clinical team members. Results: The response rate was 100%. Considerable variation existed between units for screening and management. Thirteen units (86.7%) had adopted the lower glucose tolerance values for diagnosis of GDM (fasting ≥5.1 mmol/L; two hour ≥ 8.5 mmol/L) recommended by the Scottish Intercollegiate Guidelines Network in 2010. Available data from units using the new diagnostic criteria (n = 3) revealed a significant increase in the percentage of women being diagnosed with GDM (2010: 1.28%, 2012: 2.54%; p < 0.0001). Conclusions: Despite provision of clinical guidelines there are still inconsistencies in screening and management practices across Scotland. This may reflect a lack of evidence and resources. If a similar increase in the prevalence of GDM is experienced across Scotland, there will be major implications for healthcare provision and resource allocation. Reference: Mires GJ, Williams FL, and Harper V. Screening practices for gestational diabetes mellitus in UK obstetric units. Diabet Med. 1999;16(2):138–41